PENGARUH KEPUTUSAN INVESTASI, KEPUTUSAN PENDANAAN, KEBIJAKAN DIVIDEN DAN TINGKAT SUKU BUNGA TERHADAP NILAI PERUSAHAAN - Leli Amnah Rakhimsyah; Barbara Gunawan (InFestasi, 2011)
This study aims to examine the effect of investment decisions, financing decisions, dividend policy and interest rates to corporate value. Samples are 25 companies listed in Indonesia Stock Exchange as a sample study based on purposive sampling. Criteria for the sample are a manufacturing company that went public and listed consecutively at the Indonesian Stock Exchange (BEI) in the period 2005-2009 and manufacturing companies that distribute cash dividends during the study period.Data used in this research is secondary data in the form of financial reports, the BI Rate, Fact Book, ICMD (Indonesian Capital Market Directory) and other references that support this research. Data analysis technique uses the classical assumption test: normality test, multicollinearity, autocorrelation test and the test heterocedastity. Test hypothesis using multiple regression analysis using SPSS 17.The results of this study indicate that 1) Investment decision has positive influence to corporate value. 2) Financing decision does not affect to corporate value. 3) Dividend policy has a negative and significant effect to corporate value. 4) Interest rates do not affect to corporate value.